Gloeocapsopsis aurea, a new subaerophytic cyanobacterium from maritime Antarctica - Mataloni, Maria Gabriela; Komárek, J. (Polar Biology)
The cyanobacterial microflora of maritime Antarctica appears to contain many endemic species and only few cosmopolitan or wider-distributed taxa. Several morphospecies that have been erroneously identified in the past following available keys from temperate or tropical zones belong in fact to little known and poorly described Antarctic cyanobacteria. Here we describe the taxonomy of one such example, the colonial species Gloeocapsopsis aurea.This cyanobacterium produces irregular, packet-like colonies that form black mats, films and crusts. Based on analysis of algal samples from Punta Cierva (Antarctic Peninsula) and King George Island (South Shetland Islands), this taxon is widely distributed in coastal, deglaciated areas of the maritime Antarctic. It is a important, often dominating, ecotype, mostly colonising irrigated rocks but also found in a variety of other aquatic and semi-aquatic habitats under a wide range of conductivities, pH and nutrient regimes. Fil: Mataloni, Maria Gabriela. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Ecología, Genética y Evolución. Laboratorio de Limnología; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Komárek, J. University of South Bohemia; República Checa